Neuroimmune endocrine effects of antidepressants - Antonioli M (Dove Medical Press, 2012)
Marco Antonioli, Joanna Rybka, LA CarvalhoPsychoimmunology Translational Laboratory, Health Science Research Centre, Roehampton University, London, UKAbstract: Antidepressant pharmacotherapy is to date the most often used treatment for depression, but the exact mechanism of action underlying its therapeutic effect is still unclear. Many theories have been put forward to account for depression, as well as antidepressant activity, but none of them is exhaustive. Neuroimmune endocrine impairment is found in depressed patients; high levels of circulating corticosteroids along with hyperactivation of the immune system, high levels of proinflammatory cytokines, low levels of melatonin in plasma and urine, and disentrainment of circadian rhythms have been demonstrated. Moreover, antidepressant treatment seems to correct or at least to interfere with these alterations. In this review, we summarize the complex neuroimmune endocrine and chronobiological alterations found in patients with depression and how these systems interact with each other. We also explain how antidepressant therapy can modify these systems, along with some possible mechanisms of action shown in animal and human models.Keywords: antidepressant agents, biological markers, human, cytokines, neuroinflammation, psychoneuroimmunology, endophenotype